2018
DOI: 10.1177/0748233718769806
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide exerts its cytotoxicity in NIH/3T3 fibroblast cells by apoptosis

Abstract: In conclusion, our results suggested that the IC of acrylamide against NIH/3T3 cells for 24 h was 6.73 mM and that acrylamide exerted its cytotoxic and anti-proliferative effects on these cells mainly via apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…ROS causes cell apoptosis through the regulated or non‐physiological apoptotic pathway. AA exposure not only activated the mitochondrial apoptotic pathway in PC12 cells but also triggered the downregulation of the Bcl‐2/Bax ratio, over the release of cleavage of caspase‐9 and caspase‐9 (Pan et al., 2017; Sahinturk, Kacar, Vejselova, & Kutlu, 2018). AA can induce endoplasmic reticulum (ER) stress and subsequent eIF2α‐ATF4‐CHOP signaling cascade in SH‐SY5Y cells (Komoike & Matsuoka, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…ROS causes cell apoptosis through the regulated or non‐physiological apoptotic pathway. AA exposure not only activated the mitochondrial apoptotic pathway in PC12 cells but also triggered the downregulation of the Bcl‐2/Bax ratio, over the release of cleavage of caspase‐9 and caspase‐9 (Pan et al., 2017; Sahinturk, Kacar, Vejselova, & Kutlu, 2018). AA can induce endoplasmic reticulum (ER) stress and subsequent eIF2α‐ATF4‐CHOP signaling cascade in SH‐SY5Y cells (Komoike & Matsuoka, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, NIH/3T3 cell line was another choice representing the mesenchyme‐derived cells forming the most basic unit of the connective tissues. Previously, Sahinturk, Kacar, Vejselova, and Kutlu () have used NIH/3T3 cell line for evaluating cytotoxicity of acrylamide. All the hits ( 2 , 5e , 5i , and 5m ) along with doxorubicin, representing cytotoxic drugs as positive control and vehicle as negative control, were evaluated in MTT assay using hPBMCs and NIH/3T3 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…In this study AA, increased the OH˙ levels concentration‐dependently, however, H 2 O 2 levels increased only at 1000 μM AA concentration (Figure D and E). Several reports indicated that oxidative stress‐related AA toxicity results in overproduction of intracellular ROS, lipid peroxidation and mitochondrial dysfunction . MDA, which is a biomarker of the degraded oxidant status and final product of lipid peroxidation in cells, has increased depending on the concentration of AA (Figure C).…”
Section: Discussionmentioning
confidence: 99%